European Parliament Elections in Poland in 2014 - Szczepański, Dominik (Political Preferences, 2014)
The aim of the article was discuss the elections to the European Parliament in Poland in 2014, taking into consideration the political situation before the elections in particular. The influence of the parliamentary elections in 2011 on the Polish political scene, and the activity of governmental coalition of the Civic Platform and the Polish Peasant Party, as well as the emergence of new political entities actively participating in electoral competition, has been analysed. A detailed analysis was done regarding the course of election campaign, paying attention to the elements of negative campaigning as well as the course of the elections themselves. The final reflections were dedicated to the election results and their influence (consequences) on the Polish party system. Key words: elections, European Parliament, Polish political scene, political competition, party system